Pushing Boundaries and Exploring Limits: Ami McKay’s The Birth House as (Hys)torical Fiction - Mintz, Judith Rebecca (Pivot: A Journal of Interdisciplinary Studies and Thought, 2013)
This chapter examines the structural and political devices of postmodern historiographic metafiction and the use of humorous fiction about childbirth as a counter-historical practice. I argue that while The Birth House operates as a form of historical fiction, author Ami McKay’s primary goal is to draw attention to Euro-Canadian notions of morality and the so-called medically sound infallibility of science through representations of the grotesque. What type of book is The Birth House and how does it fit in to Canadian literary tradition? I propose that The Birth House provides a space in which McKay uses binary oppositions to argue for the promotion of midwifery, holistic birthing, and the reclamation of the feminist body through mothering. Through historical fiction, McKay unpacks historic discourse by suggesting that the inscription of a woman, a midwife no less, into turn of the twentieth century narrative disrupts the national myths of medical and scientific progress.